Description Analysis of Patient Satisfaction Level With The Service Quality of The Outpatient Installation of The General Hospital, Dr. Zainoel Abidin Banda Aceh - Ariza Farizca; Martunis Martunis; Said Usman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This research is a quantitative approach to deductive mindset style research. The research was conducted from June to July 2020 in five polyclinics. Non-probability sampling with a purposeful sampling technique was the sampling method. Most research respondents rated satisfaction (81.2%) with RSUDZA polyclinic services with a range of SME 80.80 values and the overall mean level of conformity for the variable quality of service was 95 percent, with the highest reliability suitability (98.3 percent) and the lowest empathy level (98.3 percent) (92.2%). The Wilcoxon test results show that, with a p value of = 0.001, there is a significant difference between expectations and performance. Overall, RSUDZA services have a good level of satisfaction and quality. There are some elements that are missing, however. The relationship between patient expectations and the results obtained in the polyclinic service is important